Association of dietary and nutrient patterns with systemic inflammation in community dwelling adults - Wang, Yoko Brigitte; Page, Amanda J.; Gill, Tiffany K.; Melaku, Yohannes Adama (Frontiers in Nutrition, 2022)
Evidence investigating associations between dietary and nutrient patterns and inflammatory biomarkers is inconsistent and scarce. Therefore, we aimed to determine the association of dietary and nutrient patterns with inflammation. Overall, 1,792 participants from the North-West Adelaide Health Study were included in this cross-sectional study. We derived dietary and nutrient patterns from food frequency questionnaire data using principal component analysis. Multivariable ordinal logistic regression determined the association between dietary and nutrient patterns and the grade of inflammation (normal, moderate, and severe) based on C-reactive protein (CRP) values. Subgroup analyses were stratified by gender, obesity and metabolic health status. In the fully adjusted model, a plant-sourced nutrient pattern (NP) was strongly associated with a lower grade of inflammation in men (ORQ5vsQ1=0.59, 95%CI:0.38-0.93, p-trend=0.08), obesity (ORQ5vsQ1=0.43; 95%CI:0.24-0.77, p-trend =0.03) and metabolically unhealthy obesity (ORQ5vsQ1=0.24; 95%CI:0.11-0.52, p-trend=0.01). A mixed NP was positively associated with higher grade of inflammation (ORQ5vsQ1=1.35; 95%CI: 0.99-1.84, p-trend=0.03) in all participants. A prudent dietary pattern was inversely associated with a lower grade of inflammation (ORQ5vsQ1=0.72, 95%CI:0.52-1.01, p-trend=0.14). In contrast, a western dietary pattern and animal-sourced NP were associated with a higher grade of inflammation in the all participants although BMI attenuated the magnitude of association (ORQ5vsQ1=0.83, 95%CI:0.55-1.25; and ORQ5vsQ1=0.94, 95%CI:0.63-1.39, respectively) in the fully adjusted model. In conclusion, a plant-sourced NP was independently associated with lower inflammation. The association was stronger in men, and those classified as obese and metabolically unhealthy obese. Increasing consumption of plant-based foods may mitigate obesity-induced inflammation and its consequences.